1997
DOI: 10.1007/bf02934498
|View full text |Cite
|
Sign up to set email alerts
|

Multiple early esophageal cancers arising from Barrett's esophagus, and a review of cases of early adenocarcinoma in Barrett's esophagus in Japan

Abstract: A case of early esophageal adenocarcinoma arising in Barrett's esophagus is reported. Many cases of Barrett's esophagus, which is considered a premalignant condition, have been reported in Western countries, but few cases have been reported in Japan. The patient, a 53-year-old man with nausea and vomiting, was a drinker (four glasses wine/day for about 30 years), but did not smoke. He had had a hiatal hernia of the esophagus. Since endoscopic biopsies demonstrated an early adenocarcinoma in Barrett's esophagus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Metaplastic mucosa, dysplasia and adenocarcinoma were strongly intermixed confirming the metaplasia-dysplasia-carcinoma sequence in the neoplastic progression of BE. Superficial adenocarcinoma can also be multifocal [12,14]. Although it has been suggested that superficial adenocarcinoma develops most of the time close to the squamocolumnar junction [18], in our series as in other reports, adenocarcinomas occur in any part of BE including the lower part [14].…”
Section: Discussionsupporting
confidence: 48%
“…Metaplastic mucosa, dysplasia and adenocarcinoma were strongly intermixed confirming the metaplasia-dysplasia-carcinoma sequence in the neoplastic progression of BE. Superficial adenocarcinoma can also be multifocal [12,14]. Although it has been suggested that superficial adenocarcinoma develops most of the time close to the squamocolumnar junction [18], in our series as in other reports, adenocarcinomas occur in any part of BE including the lower part [14].…”
Section: Discussionsupporting
confidence: 48%
“…In Japan and Asia, the majority of esophageal carcinomas are of squamous cell origin, whereas in Western countries the reports on adenocarcinoma complicating Barrett's epithelium in relation to regurgitation esophagitis are increasing [24 -26]. Due to our limited experience with EUS on this particular category at present [27], the discussion will have to await future developments, however, the use of the miniprobe scanner will extend the possibility of early detection of adenocarcinoma complicating esophageal dysplasia of this particular disease entity.…”
Section: Discussionmentioning
confidence: 99%